CHOOSING LIVES: Pandemic Emergency Triage from the Perspective of MaqÄshid - FUADY ABDULLAH (Islamuna: Jurnal Studi Islam, 2021)
The spike in Covid-19 cases in Indonesia in mid-2021 has led to scarcity of various resources and resulted in a functional crisis of hospitals in accommodating patients. This condition puts health workers and relevant policy makers in difficult situation and ethical dilemma in triaging patients. In this context, there are at least two competing ethical approaches. The utilitarian approach demands maximum benefit in saving lives, whereas the egalitarian approach emphasizes equal rights and opportunities for treatment. This brings up several problems related to giving priority. The problems also include withdrawal of treatment in favour of other patients. This article normatively tries to discuss the issue from the MaqÄshid perspective. This article is qualitative. Literature review of several related recommendations was carried out to explore the basic problems and then putting them in light of the maqÄshid theory. This article argues that MaqÄshid can be an alternative ethical approach in determining priorities. All considerations need to be read in the light of MaqÄshid and its principles with primary focus on scientific and medical considerations. ABSTRAK Lonjakan kasus Covid-19 di Indonesia pada pertengahan tahun 2021 menyebabkan kelangkaan berbagai sumber daya dan krisis fungsional rumah sakit dalam menampung pasien. Kondisi ini menempatkan tenaga kesehatan & pengambil kebijakan berada dalam situasi sulit dan dilema etik untuk melakukan triase pasien. Dalam konteks ini, ada dua pendekatan etis yang bersaing yaitu utilitarian yang menuntut manfaat maksimal dalam menyelamatkan nyawa dan pendekatan egaliter menekankan persamaan hak dan kesempatan untuk mendapatkan perlakuan. Hal ini memunculkan beberapa permasalahan terkait pemberian prioritas. Artikel ini secara normatif mencoba membahas masalah tersebut dari perspektif MaqÄshid. Artikel ini bersifat kualitatif. Tinjauan pustaka terhadap beberapa rekomendasi terkait dilakukan untuk menggali permasalahan mendasar dan kemudian meletakkannya dalam tinjauan teori maqÄshid. Artikel ini melihat bahwa MaqÄshid dapat menjadi alternatif pendekatan etis dalam menentukan prioritas triase. Seluruh pertimbangan yang ada perlu dibaca berdasar MaqÄshid dan prinsip-prinsipnya dengan fokus utama pada pertimbangan ilmiah dan medis.